The Quality of Intertidal Sediments and Biodiversity of Macrobenthic Invertebrates - Romil T. Dandan; Renato C. Diocton (Alliance of Health Activists (AloHA), 2019)
This study describes for the first time the quality of intertidal sediments and biodiversity of macrobenthic invertebrates of Carigara Bay Eastern Visayas, Philippines. The objectives of the study were to describe and assess diversity of macrobenthic invertebrates of exposed sandy muddy beaches of the area. Macrobenthic community was collected using 0.5 m2 quadrat laid parallel with the transect line across intertidal zone in three identified station. The study showed that macrobenthic invertebrates was dominated by Mollusca 51.41-(Paphia amabilis, Tellina radiata, Pteria levanti, Nerita planopira, Scapharca sp, Modiolus metcalfe). Crustacea 14.88 (shrimps, lobster, crabs). Porifera 13.22(sponges). Cnidaria 9.09 Urticina columbiana. Annelida 8.26 (polychaetes). Echinodermata 4.13 (sea stars). Sediments structure dominated by very fine (silty, clay) which indicates normal (Kolmogorov-Smirnov). H-test was rejected from three stations computed value is greater than tabulated value. 32.5146 > 5.99, 25.99>5.99, 28.77>5.99. pH average value is 6.51 which in normal range. Organic matter average 0.16 inadequate value. Phosphorus ave. 3.1 inadequate value. Exchangeable potassium 1.04 > adequate value is 0.25 (table 5). Keywords: Intertidal, Macrobenthic, Biodiversity